FEATURES OF COLONIZATION BY THE MICROFLORA OF THE ORAL CAVITY AND INTESTINES IN THE FIRST DAYS OF BIRTH IN PREMATURE INFANTS - Musaev, A.A.; Bayramli, R.B.; Akhmedov, A.S. (World of Medicine and Biology, 2024)
2 groups of newborns were examined: the 1st (main) group included 20 newborns (15 boys, 5 girls) with an average gestational age of 30 weeks (range 25–36 weeks) and an average birth weight of 1125 g (range 560–1500 g). The 2nd (control) group included 20 healthy newborn infants (15 boys, 5 girls). In the main group, 9 infants received mother's milk, 3 artificial formula, 8 infants received parenteral nutrition; in the control group: 15 received mother's milk, 5 infants received artificial mixture. A classical bacteriological study was performed. In the microbiocenosis of the oral cavity of children born to women with intestinal and vaginal eubiosis, by the end of the first week, representatives of the resident flora were the predominant microflora: lactobacilli (100.0 %, lg 4.6±0.6 CFU/ sub unit.), bifidobacteria (75.0 %; lg 2.7±0.3 CFU/sub unit.), non-pathogenic streptococci: S.mitis (50.0 %, lg3.5±0.5 CFU/sub unit), S.salivarius (75.0 %; lg 3.2±0.2 CFU/sub unit), S.sangvis (59.7 %; lg 2.4±0.6 CFU/sub unit); coagulase-negative staphylococci: S.epidermidis (75.0 %; lg 3.4±0.6 CFU/unit sub.). Representatives of the transient microflora were found in a small percentage of observations and their contamination was insignificant: S.mutans (12.1 %; lg 2.2±0.2 CFU/sub unit), S.aureus (25.0 %; lg 2.2±0.8 CFU/sub unit), Klebsiellae (9.7 %; lg 1.4±0.4 CFU/unit.sub.), Escherichia (4.8 %; lg1.1±0.3 CFU/sub unit), fungi of the genus Candida (12.1 %; lg 2.2±0.8 CFU/ sub unit).As a result of the study, it was found that the flora of the throat and feces of premature infants at birth were predominantly gram-negative bacilli, easily installed in the faeces, and to a lesser extent in the throat.
Keywords: premature newborns; microflora of the oral cavity and intestines